Efektivitas Penyelesaian Sengketa Tanah Melalui Jalur Mediasi (Studi Penelitian Di Gampong Bumi Sari, Kec. Beutong, Kab. Nagan Raya) - Burhanuddin Burhanuddin; Rachmatika Lestari (Universitas Katolik Widya Karya Malang, 2023)
Mediation has been regulated in Perma Number 1 of 2016 Article 1 point 1 explaining mediation as an alternative way of resolving disputes through a negotiation process to obtain an agreement between the parties assisted by a mediator. Mediation seeks (win-win solution) to reach a peace agreement. However, in fact there are still many mediations that do not work effectively, one of them in Gampong Bumi Sari in several cases of dispute, they did not make a letter of conciliation resulting in another dispute case, Article 27 paragraph (1) Perma Number 1 of 2016 explains to make a written peace agreement when the mediation reaches an agreement, an increase in cases of land disputes that mediation did not complete, one of the parties to the dispute during mediation carried a sharp weapon with the family so that the mediator felt intimidated. This study aims to find out how the process of resolving land disputes through mediation in Gampong Bumi Sari, find out what are the obstacles in the process of resolving land disputes through mediation in Gampong Bumi Sari, and see the level of effectiveness of resolving land disputes through mediation in Gampong Bumi Sari. The method used in this research is the empirical method, namely examining how the law works in the community environment.